The reproductive biology and cycle of Rioraja agassizi (Müller and Henle, 1841) (Chondrichthyes: Rajidae) in southeastern Brazil, SW Atlantic Ocean - Oddone, María Cristina [UNESP]; Amorim, Alberto F.; Mancini, Patricia L.; Norbis, Walter; Velasco, Gonzalo [UNESP] (My University, 2007)
Specimens of Rioraja agassizi were collected at Guarujá pier, São Paulo State, Brazil, from March 2005 to March 2006. A total of 275 males were captured. Based on the analysis of the clasper length, gonad weight, clasper gland length, alar thorns and lobule diameter, the size-at-maturity was estimated to be 32 cm. There were 1049 females in the record. Size-at-maturity was calculated in 40 cm. Sexual resting females were observed. Gonadosomatic and hepatosomatic indexes varied significantly in both sexes throughout the year. However, ovulation, egg-laying and presence of sperm in the seminal vesicle were observed all year round. For this reason, an annual cycle with at least one peak in the sexual activity is proposed for this species.
Keywords: Clasper; Clasper gland; Egg-bearing; Elasmobranchs; Gonads; Nidamental gland; Vitellogenic follicles; fish; gamete; reproductive biology; reproductive cycle; sexual behavior; sexual reproduction; size at maturity; Atlantic Ocean; Brazil; Sao Paulo [Brazil]; South America; Chondrichthyes; Elasmobranchii; Rajidae; Rioraja